Blood molecular markers associated with COVID‐19 immunopathology and multi‐organ damage. (14th December 2020) - Chen, Yan‐Mei; Zheng, Yuanting; Yu, Ying; Wang, Yunzhi; Huang, Qingxia; Qian, Feng; Sun, Lei; Song, Zhi‐Gang; Chen, Ziyin; Feng, Jinwen; An, Yanpeng; Yang, Jingcheng; et al.
Abstract: COVID‐19 is characterized by dysregulated immune responses, metabolic dysfunction and adverse effects on the function of multiple organs. To understand host responses to COVID‐19 pathophysiology, we combined transcriptomics, proteomics, and metabolomics to identify molecular markers in peripheral blood and plasma samples of 66 COVID‐19‐infected patients experiencing a range of disease severities and 17 healthy controls. A large number of expressed genes, proteins, metabolites, and extracellular RNAs (exRNAs) exhibit strong associations with various clinical parameters. Multiple sets of tissue‐specific proteins and exRNAs varied significantly in both mild and severe patients suggesting a potential impact on tissue function. Chronic activation of neutrophils, IFN‐I signaling, and a high level of inflammatory cytokines were observed in patients with severe disease progression. In contrast, COVID‐19‐infected patients experiencing milder disease symptoms showed robust T‐cell responses. Finally, we identified genes, proteins, and exRNAs as potential biomarkers that might assist in predicting the prognosis of SARS‐CoV‐2 infection. These data refine our understanding of the pathophysiology and clinical progress of COVID‐19. SYNOPSIS: Proteomics, metabolomics and RNAseq data map immune responses in COVID‐19 patients with different disease severity, revealing molecular makers associated with disease progression and alterations of tissue‐specific proteins. A multi‐omics profiling of the host response to SARS‐CoV2 infection in 66 clinically diagnosed and laboratory confirmed COVID‐19 patients and 17 uninfected controls. Significant correlations between multi‐omics data and key clinical parameters. Alteration of tissue‐specific proteins and exRNAs. Enhanced activation of immune responses is associated with COVID‐19 pathogenesis. Biomarkers to predict COVID‐19 clinical outcomes pending clinical validation as prospective marker. Abstract : Proteomics, metabolomics and RNAseq data map immune responses in COVID‐19 patients with different disease severity, revealing molecular makers associated with disease progression and alterations of tissue‐specific proteins.